The Effect of Spiritual Well-Being on Self-care Agency in Chronic Obstructive Pulmonary Patients in Turkey: The Mediating Role of Psychological Resilience - Öztürk, Zeynep Duygu (Journal of religion and health, 2024)
The aim of the present study was to determine the mediator role of psychological resilience in examining the effect of spiritual well-being on self-care agency in Chronic Obstructive Pulmonary Patients (COPD). The present cross-sectional and correlational study has a descriptive design, and it was conducted with 200 COPD patients admitted to the chest diseases outpatient clinic of a university hospital. "Spiritual Well-Being Scale (FACIT Sp-12)," "Brief Resilience Scale (BRS)" and "Self-Care Agency Scale (SCAS)" were used in the study for collecting the research data. STROBE recommendations were followed while reporting this study. FACIT Sp-12 total score average, the BRS total average score and the ASAS total average score of the patients were found to be 29.88 ± 1.44, 21.47 ± 66.31, and 84.81 ± 14.69, respectively. In addition, it was determined that both spiritual well-being (β = 0.170) and psychological resilience (β = 0.777) positively affected self-care agency. SCAS mediates the effect of FACIT-Sp-12 on self-care agency and strengthens the positive effect of FACIT-Sp-12 on self-care agency (β = 0.843). It was seen that the predictive effect of these two variables in explaining self-care power was 60%. Spiritual well-being and self-care agency of the COPD patients were found to be moderate, and the psychological resilience was found to be high. In addition, spiritual well-being was found to affect self-care agency directly and the mediating role of psychological resilience indirectly.